Long Term Observation of Atmospheric Aerosols at Sakai, Osaka, Japan - Ito, Norio; Mizohata, Akira (Journal of the Institute of Engineering, 2012)
We have continuously observed the aerosols with 3 kinds of samplers; automatic daily sampler (DS), Andersen sampler (AS) and Low pressure Andersen Sampler (LPAS) at Sakai, Osaka, Japan. We started these sampling from 1986 (DS), 1993 (AS) and 2000 (LPAS). Yearly mean of fine particles (< 2.1μm) has decreased by about 10 μg/m3 from 1993 to 2009. By contrast the coarse particles (> 2.1μm) do not have explicit decrease. The main constituents in fine particles are carbon matters (EC and OC) and ions (sulphate and nitrate). Ions do not have decrease trend. These trends indicate that the decrease of fine particles might be caused by the decrease of carbon matters. DOI: http://dx.doi.org/10.3126/jie.v8i3.5933 JIE 2011; 8(3): 72-74